Peran Dosen Native Speaker dalam Pembelajaran Bahasa Arab di Perguruan Tinggi - Taflilah, Dina; Nordin, Puan Farah Nadiah (Alsina : Journal of Arabic Studies, 2024)
This study aims to describe the implementation of Arabic language teaching by native speakers in the Arabic Language Education Program at UIN Walisongo Semarang, the role of native speaker instructors, and the students’ responses to the presence of native speakers in Arabic language instruction. This research employs a mixed-method approach with field research. For the qualitative part, data were collected through observation, interviews, and documentation. As for the quantitative aspect, data were gathered using questionnaires distributed to 24 students from the 6th-semester ICP class. In Arabic language instruction, the native speaker plays the roles of teacher, source of information, learning motivator, facilitator, and provider of insights into Arab countries, particularly Egypt.